2012
DOI: 10.1017/s1751731111002679
|View full text |Cite
|
Sign up to set email alerts
|

Pre-analytical factors affecting the results of laboratory blood analyses in farm animal veterinary diagnostics

Abstract: The quality of the laboratory diagnostic approach in farm animals can be severely affected by pre-analytical factors of variation. They induce increase/decrease of biochemical and hematological analyte concentrations and, as a consequence, they may cause unsuitable conclusions and decisions for animal health management and research projects. The pre-analytical period covers the preparation of sampling, the sampling procedure itself, as well as all specimen handling until the beginning of the specific laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 71 publications
2
16
0
2
Order By: Relevance
“…The use of pool samples is an ongoing discussion in farm animal diagnostics [14,15]. As expected from the methodical point of view, our results showed that pooling of five samples correlated well with the mean of the same samples analysed individually for Se concentration.…”
Section: Discussionsupporting
confidence: 83%
“…The use of pool samples is an ongoing discussion in farm animal diagnostics [14,15]. As expected from the methodical point of view, our results showed that pooling of five samples correlated well with the mean of the same samples analysed individually for Se concentration.…”
Section: Discussionsupporting
confidence: 83%
“…In veterinary clinical pathology, book chapters in standard textbooks refer to preanalytic variability, but often the provided information is not referenced to original articles. In addition, there are some review articles for domestic or laboratory animals, and recommendations with guidelines for quality control of preanalytic, analytic, and postanalytic phases have been published by the American Society of Veterinary Clinical Pathology (ASVCP) . However, the provided information is often general, and details can only be found in original studies.…”
Section: Available Information On Preanalytic Variability In Veterinamentioning
confidence: 99%
“…In addition, the study also aimed to establish the degree of individual variation within populations and if pre‐analytical treatments could cause false diagnosis of disease. Moreover, a standardized methodology of sampling and specimen care is proposed that is in line with established protocols for use in other livestock production sectors but not, so far, in aquaculture (Humann‐Ziehank & Ganter ).…”
Section: Introductionmentioning
confidence: 99%